Impact of quantum non‐locality and electronic non‐ideality on e–He scattering in a dense plasma. Issue 2 (1st February 2018) - Ramazanov, Tlekkabul S.; Amirov, Samat M.; Moldabekov, Zhandos A.
Abstract : The screened Hartree–Fock potential and the polarization potential for the description of the electron–helium scattering in dense plasmas are derived. The effects of quantum non‐locality and correlations of free electrons are taken into account in the plasma dielectric function. Plasma polarization leads to a significant increase in the transport cross‐section at small wave numbers ka  < 2 in comparison with the case of an electron scattering on the isolated atom, where a is the mean distance between plasma electrons. It is shown that taking into account the quantum non‐locality and correlations is important at ka  < 2.